Determinação de ações preventivas pela aplicação do método FMEA na análise de riscos na construção civil - Zaupa, Juliana Caroline Teixeira (2023)
According to 2021 Social Security statistics, the number of work accidents in Brazil remains high. In this context, when it comes to health and safety management in civil construction, risk management is highly important in risk analysis for accident prevention. Focusing on this issue, this research was carried out in the civil construction sector between 2021 and 2022, having as its theme the determination of preventive actions by applying the FMEA method in risk analysis in civil construction and as a general objective to determine relative preventive actions work safety, detected by the application of the Failure Mode and Effect Analysis method – FMEA (Failure Mode and Effect Analysis), for civil construction works. In order to obtain data, observational and photographic records were made in the works analyzed in relation to the risks to which workers are exposed. Subsequently, it was verified that there was a similarity regarding the types of risks found, regardless of whether the work was medium or large and also that in the analysis of the priority of risks with the application of the FMEA method, using the severity and detection indexes proposed by Cavaignac and Uchoa (2018) and the scale of occurrence pointed out by Palady (2002), most of the high RPNs (Risk Priority Numbers) were related to stairs (inadequate structure or lack of protection), ranging between 90 and 100, since this situation was more serious because it also included people not involved in the work process. Thus, it could be concluded that the FMEA method contributed to the determination and prioritization of preventive actions related to work safety for the civil construction works analyzed.